Bild - Skulpturen - Bild : Neuere Aspekte plastischer Kunst in der Sammlung Jung, Aachen. - Jung, Hugo; Schneider, Ulrich (Aachen : Suermondt-Ludwig-Museum Aachen, 1996)
Förg, Gunther ; Carroll, Lawrence ; Judd, Donald ; Ruthenbeck, Reiner ; Knoebel, Imi ; Andre, Carl ; Cragg, Tony (Anthony) ; Kounellis, Jannis ; Nauman, Bruce ; Fischli & Weiss ; West, Franz ; Whiteread, Rachel
biografie
Bild - Skulpturen - Bild : Neuere Aspekte plastischer Kunst in der Sammlung Jung, Aachen, Suermondt-Ludwig-Museum, Aachen, 10. Februar - 21. April 1996
Duits
boek